Modern Management of Anthracycline‐Induced Cardiotoxicity in Lymphoma Patients: Low Occurrence of Cardiotoxicity with Comprehensive Assessment and Tailored Substitution by Nonpegylated Liposomal Doxorubicin. (8th March 2017) - Olivieri, Jacopo; Perna, Gian Piero; Bocci, Caterina; Montevecchi, Claudia; Olivieri, Attilio; Leoni, Pietro; Gini, Guido
Abstract : Background: Anthracyclines (AC) are still undeniable drugs in lymphoma treatment, despite occasionally causing cardiotoxicity. Liposomal AC may reduce cardiotoxicity while retaining clinical efficacy; also, biomarker monitoring during chemotherapy allows early detection of cardiac damage, enabling strategies to prevent left ventricular ejection fraction (LVEF) deterioration. Materials and Methods: We conducted a prospective observational trial in a real‐life population of lymphoma patients, combining advanced echocardiography and biomarkers (Troponin I [TnI]) for early detection of cardiotoxicity; we applied a prespecified policy to minimize cardiotoxicity, selecting patients with higher baseline risk to replace doxorubicin with nonpegylated liposomal doxorubicin (NPLD) and starting cardioprotective treatment when subclinical cardiotoxicity was detected. Results: Ninety‐nine patients received ≥1 cycle of chemotherapy (39 with NPLD): 38 (NPLD = 34) were older than 65 years. At baseline, the NPLD subgroup had more cardiovascular risk factors and comorbidities than the doxorubicin subgroup. After treatment, echocardiographic parameters did not worsen in the NPLD subgroup; significant LVEF reduction occurred in two patients treated with doxorubicin. Over treatment course, TnI rises increased linearly in the doxorubicin subgroup but modestly in the NPLD subgroup. At doxorubicin doses >200 mg/m 2 the difference was statistically significant, with more TnI rises in the doxorubicin subgroup. NPLD‐treated patients did not experience higher rates of grade 3–4 adverse events. Within the diffuse large B‐cell lymphomas category, we observed similar rates of complete and overall responses between doxorubicin‐ and NPLD‐treated patients. Conclusion: A comprehensive strategy to prevent, detect, and treat cardiotoxicity allows an optimal management of the lymphoma with low incidence of cardiac complications. Abstract : The aim of this study was to quantify the occurrence of cardiotoxicity in a real‐life population of lymphoma patients, combining novel and traditional monitoring methods, including clinical, echocardiographic, and laboratory parameters. Comprehensive management of anthracycline‐induced cardiotoxicity consisted of a tailored use of liposomal doxorubicin in high‐risk patients, a combined monitoring approach integrated through a telemedicine system, and preemptive treatment of subclinical cardiotoxicity with beta‐blockers or renin‐angiotensin system inhibitors.